In vitro pharmacological characterization of SPN-810M (molindone) - Yu C; Gopalakrishnan G (Dove Medical Press, 2018)
Chungping Yu,1 Gopakumar Gopalakrishnan2 1Preclinical DMPK and Pharmacology, Supernus Pharmaceuticals, Inc., Rockville, MD, USA; 2Preclinical Toxicology, Supernus Pharmaceuticals, Inc., Rockville, MD, USA Background: Impulsive aggression (IA) is considered a maladaptive form of aggression that is reactive and overt and occurs outside of the acceptable social context. Many children and adolescents with attention-deficit/hyperactivity disorder (ADHD) display clinically significant aggression, with the predominant subtype being IA. However, there is currently no Food and Drug Administration-approved medication specifically to treat IA. The pathophysiology of IA is not fully understood, although it has been suggested to include the dopamine, norepinephrine, and serotonin systems. Methods: SPN-810 (extended-release molindone) is being developed for the novel indication of IA and is currently being studied in patients treated for ADHD. Molindone is an indole derivative and a dopamine D2 receptor antagonist. Results: The in vitro pharmacological studies described in the current manuscript demonstrate that the active substance molindone (SPN-810M) is a potent antagonist for the dopamine receptors, D2S and D2L, and the serotonin receptor, 5-HT2B, at therapeutic concentrations. The in vitro studies further demonstrate that the antagonist effect of SPN-810M is due to the parent drug and not the metabolites, and that the antagonism is not affected by the presence of norepinephrine or dopamine neurotransmitters. In addition, studies investigating the potential differential effects of the enantiomers of SPN-810M have demonstrated that the R(−) enantiomer is more potent than S(+), showing greater regulatory effect on D2S and D2L receptors. Conclusion: Overall, the results of the in vitro SPN-810M pharmacological studies provide some insight into how SPN-810M modulates the serotonin and dopamine pathways that play a role in IA. Keywords: dopamine, serotonin, SPN-810M, impulsive aggression